Exploring Mediating Role of Green Supply Chain Management between Political Support by Government, Green Knowledge Management Capability and Sustainable Competitive advantage - Siahaan, Chontina; Samosir, Osbin; Ali, Hapzi (International Journal of Supply Chain Management, 2020)
The main purpose of this study is to examine the relationship between green knowledge management capability, top management support, Political Support by the government, green entrepreneurial orientation, green supply chain management and sustainable competitive advantage. Moreover, the present research also examined the mediating role of green supply chain management as well. The data of the present study were gathered in the form of survey questionnaires from the employees of the textile sector of Indonesia through convenience sampling. From the distributed questionnaires, 560 usable questionnaires were received back. Thus, the response rate of the present study was 62.5%. The researcher employed PLS-SEM technique for the analysis of the data. It’s been revealed from the findings of the study that all proposed direct hypothesis was supported significantly. Moreover, the mediating role of green supply chain management between green knowledge management capability, top management support, Political Support by the government, green entrepreneurial orientation and sustainable competitive advantage was also supported statistically. The findings of the study fill the gap of limited studies conducted regarding government policy in the context of the supply chain. Moreover, the results of the present study are helpful for the policymakers of the textile sector to enhance their profit by minimizing the impact on the environment.